2008
DOI: 10.1021/jf802037f
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Dietary Fiber Components in Barley Varieties in the HEALTHGRAIN Diversity Screen

Abstract: Ten different barley varieties grown in one location were studied for their content of tocols, folate, plant sterols, alkylresorcinols, and phenolic acids, as well as dietary fiber components (arabinoxylan and beta-glucan). The samples included hulled and hull-less barley types and types with normal, high-amylose, and waxy starch. The aim was to study the composition of raw materials, and therefore the hulls were not removed from the hulled barleys. A large variation was observed in the contents of all phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
132
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(156 citation statements)
references
References 69 publications
15
132
1
8
Order By: Relevance
“…More precisely, waxy barley cultivars possess higher levels of water and acid extractable β-glucans than regular barleys (Ajithkumar et al, 2005;Izydorczyk et al, 2000). Our results are consistent with previously published studies (Andersson et al, 2008;Gao et al, 2009). …”
Section: Analyses Of Three Consecutive Harvestssupporting
confidence: 93%
See 2 more Smart Citations
“…More precisely, waxy barley cultivars possess higher levels of water and acid extractable β-glucans than regular barleys (Ajithkumar et al, 2005;Izydorczyk et al, 2000). Our results are consistent with previously published studies (Andersson et al, 2008;Gao et al, 2009). …”
Section: Analyses Of Three Consecutive Harvestssupporting
confidence: 93%
“…With that wide range, barley genotypes are between the ranges of wheat and rye. Holtekjølen et al (2006) found generally higher values for hulless genotypes and this observation was later on confirmed within the HEALTHGRAIN diversity screen (Andersson et al, 2008). Water-extractable pentosanes (we-PENT) were a minor constituent ranging from 0.1% (Taiga) to 1.1% (Purple Nudum).…”
Section: Analyses Of Three Consecutive Harvestsmentioning
confidence: 63%
See 1 more Smart Citation
“…α-, β+γ-, -tocopherols and α-, β+γ-, δ-tocotrienols that protect the caryopsis against oxidation during storage and germination [6,7,8,9,10], this is important for malt production. Peterson [8] claims that α-tocopherol isomer and a smaller amounts of γ-, δ-tocopherols and β-tocotrienols are contained in a caryopsis germ.…”
Section: Statistická Analýzamentioning
confidence: 99%
“…Je zajímavé, že právě v zrnu ječmene je zastoupeno všech osm izomerů vitamínu E, tj. α-, β+γ-, δ-tokoferoly a α-, β+γ-, δ-tokotrienoly, které chrání obilku před oxidací během skladování a klíčení [6,7,8,9,10], což je důležité pro výrobu sladu. Peterson [8] udává, že v klíčku obilky je obsažen izomer α-tokoferol a menší množství γ-, δ-tokoferolů a β-tokotrienolu.…”
unclassified